Plan de desarrollo turístico comunitario para la Parroquia Santa Maria, Manga del Cura Provincia de Manabí - Quiroz Rodriguez, Lourdes Elizabeth (2021)
The province of Manabí is one of the most beautiful and touristic corners of Ecuador that the country can offer, its beaches and tourist attractions are a point of national and international interest, having this a port where it can receive important tourist ships, this positions it as a canton with a beach appeal of excellence, however this tourism photo is not the only one offered by the province, over the years this attraction has only been promoted as a focus of progress and pride, but the composition of the province it can offer much more to tourists looking for other types of tourist adventures. The communities of Manabí have been hit in recent years by various problems, the lack of road infrastructure followed by various internal and external factors have generated serious problems for the development of communities, being entire communities underdeveloped and abandoned, but with rich potential in tourism; Despite the difficulties, the communities seek to develop spaces for interaction with tourist attractions. The "Manga del Cura" is a jewel of tourism that was in dispute for its provincial territorial membership for many years, this stopped the development of tourism access and promotion work, the aforementioned territorial section has areas of high value tourist interest such as its famous waterfall "El Salto del Armadillo" which is one of the largest and most impressive in Ecuador. The Santa María parish is a segmentation of La Manga del Cura, this population being mainly dedicated to livestock and agricultural activities, but due to its geographical position it has value of exploitation interest in community tourism projects, therefore this project seeks to generate an analysis to determine the community tourism development potential of this parish for the benefit of La Manga del Cura and Manabí.